2016
DOI: 10.1038/gim.2016.32
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype in patients with Noonan syndrome and a RIT1 mutation

Abstract: RIT1 is one of the major genes for NS. The RIT1-associated phenotype differs gradually from other NS subtypes, with a high prevalence of cardiovascular manifestations, especially hypertrophic cardiomyopathy, and lymphatic problems.Genet Med 18 12, 1226-1234.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
87
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 40 publications
(84 reference statements)
9
87
0
2
Order By: Relevance
“…Four novel missense pathogenic variants in the RIT1 gene were detected in our study and evaluated as disease‐related variants. Recent research showed that short stature (31%), intellectual problems (27%), and pectus anomalies (42%) were less frequent in RIT1 group patients but there was a high prevalence of HCM (42%) and lymphatic problems . Similar results were observed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Four novel missense pathogenic variants in the RIT1 gene were detected in our study and evaluated as disease‐related variants. Recent research showed that short stature (31%), intellectual problems (27%), and pectus anomalies (42%) were less frequent in RIT1 group patients but there was a high prevalence of HCM (42%) and lymphatic problems . Similar results were observed in this study.…”
Section: Discussionsupporting
confidence: 89%
“…According to the Developmental Disorders Genotype-Phenotype Database, the genes LMNA , NTRK1, and RIT1 are confirmed as causing developmental disorders in multiple unrelated cases [Indo et al, 1997;Aoki et al, 2013;Kouz et al, 2016]. There is currently no literature to support a haploinsufficient effect of RIT1 .…”
Section: Discussionmentioning
confidence: 99%
“…phenotype of pulmonary valve stenosis rather than cardiac hypertrophy, there are at least 9 additional NS-susceptibility genes, including SOS1 (7,8), RAF1 (9,10), KRAS (11), RIT1 (12,13), NRAS (14), RRAS (15), CBL (16), and SOS2 and LZTR1 (17). A mutation in SHOC2 is responsible for NS-like disorder with loose anagen hair (NS-LAH; MIM 607721) (18).…”
Section: Introductionmentioning
confidence: 99%